Photobiomodulation in the Metabolism of Lipopolysaccharides-exposed Epithelial Cells and Gingival Fibroblasts - Pansani, Taisa Nogueira [UNESP]; Basso, Fernanda Gonçalves [UNESP]; Soares, Diana Gabriela [UNESP]; Turrioni, Ana Paula da Silveira; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Wiley, 2018)
This study assessed the effects of photobiomodulation (PBM) to cells previously exposed to lipopolysaccharides (LPS). Human gingival fibroblasts (HGF) and epithelial cells (HaCaT) were seeded in wells of 24-well plates containing complete culture medium (DMEM). After 24 h, the DMEM was replaced by serum-free DMEM, and cells were exposed to LPS of Escherichia coli (E. coli) (10 μg mL−1) for 24, 48, and 72 h. The cells were subjected to specific parameters of phototherapy (PT) (LASERTable—InGaAsP—780 ± 3 nm, 25 mW, 3 J cm−2). Cell proliferation (alamarBlue®), viability (Trypan Blue) and synthesis of CCL2 (ELISA) were evaluated. Data were statistically analyzed by the Kruskal–Wallis and Mann–Whitney test (α = 5%). Proliferation and viability of both cell lines decreased after LPS treatment at 48 and 72 h. Enhanced synthesis of CCL2 by gingival fibroblasts occurred at 24 h, while epithelial cells increased synthesis of this chemokine at 48 and 72 h. PBM enhanced cell proliferation and viability in a time-dependent manner for both cell lines exposed or not to LPS, while synthesis of CCL2 by cells exposed to PT decreased over time. PBM caused biomodulatory effects on gingival fibroblasts and epithelial cells previously treated with LPS. These effects may decrease tissue inflammatory response and accelerate wound healing of oral mucosal tissue.